Preliminary Support for a Cognitive Remediation Intervention for Women During the Menopausal Transition: A Pilot Study - Ballantyne, Elena C.; King, Jelena P.; Green, Sheryl M. (Frontiers in Global Women's Health, 2021)
Background: Menopause is associated with physical and emotional symptoms, and subjective cognitive concerns that are generally not borne out on objective cognitive measures. This discrepancy suggests that a psychological rather than biological mechanism likely mediates the cognitive concerns of women in menopause. The current study assessed the feasibility and effectiveness of a cognitive remediation intervention with the goal of reducing subjective perceptions of cognitive difficulty during the menopause. Methods: Twenty-seven menopausal women (M age=53.74, SD=4.14) completed a five-week group-based intervention (with a post-group booster) consisting of 2-hour weekly sessions. Participants completed pre- and post-intervention measures capturing subjective cognitive ability, mood, anxiety, stress, personality, and objective cognitive tests. The primary variable of interest was self-reported cognitive confidence measured by the Memory and Cognitive Confidence Scale (MACCS). Results: All but one MACCS subscale significantly decreased over the course of treatment (with lower scores associated with higher confidence) and effect sizes ranged from small to large (d=-.39 to -.91) with gains maintained at one-month follow-up. Interestingly, no change in objective cognitive test performance was observed, indicating increases in subjective cognitive confidence in the absence of objective cognitive improvement. There was no change in mood, anxiety, or stress scores. Two-level HLM analyses revealed that those with higher baseline neuroticism, as measured by the NEO Personality Inventory, had smaller decreases in post-group MACCS High Standards subscale relative to those with lower baseline neuroticism (p=.027, d=-.45). Those with higher baseline depression scores on the Depression Anxiety Stress Scale (DASS-21) had a smaller decrease in post-intervention MACCS Total Score relative to those with lower depression ratings. Conclusion: To our knowledge, this is the first feasibility study of its kind targeting perceptions of cognitive impairment during menopause. Although generally well tolerated, recruitment and scheduling difficulties were flagged as challenges to engagement while a small sample size and lack of control group limit conclusions about efficacy. Providing current results could be replicated with enhanced methods, these results provide support that cognitive remediation is a feasible and credible treatment, and may improve quality of life for women in menopause.